Potential of Marine Terpenoids against SARS-CoV-2: An In Silico Drug Development Approach - Alaka Sahoo (MDPI AG, 2021)
In an emergency, drug repurposing is the best alternative option against newly emerged severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2) infection. However, several bioactive natural products have shown potential against SARS-CoV-2 in recent studies. The present study selected sixty-eight broad-spectrum antiviral marine terpenoids and performed molecular docking against two novel SARS-CoV-2 enzymes (main protease or Mpro or 3CLpro) and RNA-dependent RNA polymerase (RdRp). In addition, the present study analysed the physiochemical-toxicity-pharmacokinetic profile, structural activity relationship, and phylogenetic tree with various computational tools to select the ‘lead’ candidate. The genomic diversity study with multiple sequence analyses and phylogenetic tree confirmed that the newly emerged SARS-CoV-2 strain was up to 96% structurally similar to existing CoV-strains. Furthermore, the anti-SARS-CoV-2 potency based on a protein−ligand docking score (kcal/mol) exposed that the marine terpenoid brevione F (−8.4) and stachyflin (−8.4) exhibited similar activity with the reference antiviral drugs lopinavir (−8.4) and darunavir (−7.5) against the target SARS−CoV−Mpro. Similarly, marine terpenoids such as xiamycin (−9.3), thyrsiferol (−9.2), liouvilloside B (−8.9), liouvilloside A (−8.8), and stachyflin (−8.7) exhibited comparatively higher docking scores than the referral drug remdesivir (−7.4), and favipiravir (−5.7) against the target SARS-CoV-2−RdRp. The above in silico investigations concluded that stachyflin is the most ‘lead’ candidate with the most potential against SARS-CoV-2. Previously, stachyflin also exhibited potential activity against HSV-1 and CoV-A59 within IC50, 0.16–0.82 µM. Therefore, some additional pharmacological studies are needed to develop ‘stachyflin’ as a drug against SARS-CoV-2.